From Solutions to Linear Ordinary Differential Equations to Vertex Operators - Salehyan, Parham [UNESP] (Springer Nature, 2023)
Using the canonical isomorphism between the exterior power of solutions to generic linear Ordinary Differential Equations of order r< ∞ and the polynomial ring with r indeterminates, we define and compute certain vertex operators whose expression for r= ∞ is precisely that occurring in the classical treatment of the boson-fermion correspondence.
Keywords: Boson–Fermion correspondence; ODE; Vertex operators